Understanding the effect of pre-sintering scanning strategy on the relative density of Zr-modified Al7075 processed by laser powder bed fusion - Nicolas Nothomb; Ignacio Rodriguez-Barber; María Teresa Pérez-Prado; Norberto Jimenez Mena; Grzegorz Pyka; Aude Simar (Additive Manufacturing Letters)
Only a limited aluminium material palette is currently available for L-PBF processing, especially for high strength aluminium alloy. Unmodified Al7075 suffers from hot cracking making it nearly impossible to process by L-PBF. Adding some grain refiner to Al7075 solves this issue of hot cracking. However, this alloy still presents difficulties to be processed with densities above 99.5%. In this study, the unconventional pre-sintering scanning strategy is applied to process 99.9% density Al7075+1.8%Zr. For this scanning strategy, each layer is scanned twice with different power, i.e. it is first scanned with half the power selected for the second scan. This specific strategy remelts potential defect generated by the first scan and reduces lack of fusion pores. These two phenomena lead to high density L-PBF Al7075+1.8%Zr and pave the way to higher densities for high strength aluminium alloys.